2014
DOI: 10.1111/zoj.12166
|View full text |Cite
|
Sign up to set email alerts
|

Early fossils illuminate character evolution and interrelationships of Lampridiformes (Teleostei, Acanthomorpha)

Abstract: Lampridiformes is a peculiar clade of pelagic marine acanthomorph (spiny‐rayed) teleosts. Its phylogenetic position remains ambiguous, and varies depending on the type of data (morphological or molecular) used to infer interrelationships. Because the extreme morphological specializations of lampridiforms may have overwritten the ancestral features of the group with a bearing on its relationships, the inclusion of fossils that exhibit primitive character state combinations for the group as a whole is vital in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 41 publications
4
44
0
Order By: Relevance
“…It does not show some of the synapomorphies of the larger clade Lampridomorpha (Davesne et al . ; Delbarre et al . ), such as the overlap of the caudal‐fin rays with the caudal skeleton (hypurostegy).…”
Section: Systematic Position Of †Bajaichthysmentioning
confidence: 99%
See 1 more Smart Citation
“…It does not show some of the synapomorphies of the larger clade Lampridomorpha (Davesne et al . ; Delbarre et al . ), such as the overlap of the caudal‐fin rays with the caudal skeleton (hypurostegy).…”
Section: Systematic Position Of †Bajaichthysmentioning
confidence: 99%
“…; Davesne et al . , ): (1) there is no frontal ‘vault’; (2) the mesethmoid expands anteriorly and posteriorly to the lateral ethmoids, while in modern lampridiforms it only expands posteriorly; (3) the articulation between the anterior ceratohyal and the ventral hypohyal is not condylar; (4) the anteriormost dorsal‐fin pterygiophore inserts posterior to the first neural spine. Additional features, found in all Lampridiformes except for Veliferidae (Olney et al .…”
Section: Systematic Position Of †Bajaichthysmentioning
confidence: 99%
“…These radiations concern the Stomiatii (five new families), basal Ctenosquamata (four families), Percopsiformes (two families) and, among euacanthomorphs the polymixiids and beryciforms (three families) and a clade of stem tetraodontiforms (three families). A recent morphological phylogenetic analysis of basal acanthomorphs (Davesne et al, 2014) found a large clade called Lampridomorpha. Although this clade gathers genera in a different arrangement from the one used here, the signal indicates that radiations affected only specific clades, and not the whole range of teleosteans.…”
Section: (C) Late Cretaceous 'Fish' Diversity Patternmentioning
confidence: 99%
“…Smith Woodward's classification included a Scombriformes containing a variety of lineages now recognized as constituting a polyphyletic assemblage. Apart from a Scombridae equivalent in composition to the 'core' Scombroidei of current usage (Scombridae + Gempylidae + Trichiuridae), Smith Woodward's Scombriformes included carangids, menids, stromateoids and xiphioids, as well as taxa now recognized as pleuronectiforms (Friedman 2008), polymixiids (Patterson 1964) and lampridiforms (Davesne et al 2014). Smith Woodward's Catalogue represented a substantial increase in the diversity of mackerel-like taxa known from the London Clay, adding four new genera to Agassiz's Sphyraenodus: Eothynnus (now interpreted as a carangid ;Bannikov 1979), Scombrinus, Eocoelopoma and Scombramphodon.…”
mentioning
confidence: 99%